Development of Guided Inquiry Learning Model Based on Educational Games to Improve Elementary Students' Science Process Skills - Muspratiwi Pertiwi MR; Patta Bundu; M. Yahya (Institute of Advanced Knowledge and Science, 2024)
This research aims to develop a Guided Inquiry Learning Model Based on Educational Games, presented in a book format and supported by educational games accessible via Canva and Wordwall platforms. The model is designed to be valid, practical, and effective in enhancing elementary school students' science process skills. This study uses a Research and Development (R&D) approach, adapting the Plomp model's development stages: initial investigation, design, realization, testing, evaluation, revision, and implementation. The subjects are fifth-grade students from UPT SD Negeri 214, UPT SD Negeri 99, and UPT SD Negeri 101 in Pinrang Regency. Research instruments include validation sheets, observation sheets, questionnaires, and evaluation sheets. The study produces an Inquiry-Based Educational Game (IGE) textbook and learning tools, such as lesson plans (RPP), student worksheets (LKPD), and educational games. The findings reveal a strong need among teachers and students for a learning model that enhances science process skills. The developed IGE model comprises syntax, social system, reaction principles, support system, instructional impact, and accompanying impact. The syntax includes Activation, Playing, Exploring, and Wrap-Up phases. The IGE model meets the criteria for validity and practicality, receiving high validation ratings. The model effectively enhances students' science process skills, as shown by significant improvements in student performance. The IGE model and its learning tools are deemed highly practical, based on feedback from students and teachers.